2006
DOI: 10.1111/j.1365-2664.2005.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between yellowhammer breeding performance, arthropod abundance and insecticide applications on arable farmland

Abstract: Summary1. The UK population of yellowhammers has declined since the mid-1980s. Concurrent increases in the use of pesticides are believed to have reduced the availability of food resources for farmland birds, including yellowhammers. To mitigate the consequences of insecticide applications on yellowhammer productivity, the relationships between insecticide application, arthropod food abundance and breeding success require quantification. 2. We studied nesting yellowhammers on a lowland arable farm in North Yor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 29 publications
4
89
0
1
Order By: Relevance
“…The present data are the first results to demonstrate a link between provisioning with cereal grain and reduced Yellowhammer nestling body condition. Although cereal grain is plentiful and easily collected, the energy content of barley and wheat are both lower than that of invertebrates (Potts 1986, Hart et al 2006, as is the protein content of wheat (Potts 1986). The low protein content of grain is likely to be a limiting factor because nestlings require food that is rich in protein and specific amino acids, which may be lacking in plant food (Ricklefs 1983, Potts 1986.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The present data are the first results to demonstrate a link between provisioning with cereal grain and reduced Yellowhammer nestling body condition. Although cereal grain is plentiful and easily collected, the energy content of barley and wheat are both lower than that of invertebrates (Potts 1986, Hart et al 2006, as is the protein content of wheat (Potts 1986). The low protein content of grain is likely to be a limiting factor because nestlings require food that is rich in protein and specific amino acids, which may be lacking in plant food (Ricklefs 1983, Potts 1986.…”
mentioning
confidence: 99%
“…Invertebrate availability can, however, be highly variable owing to factors such as habitat, season, weather and management practices (Bryant & Turner 1982, Hart et al 2006. In agricultural landscapes, for example, management intensification over recent decades has reduced the abundance and accessibility of invertebrate food, contributing to population declines in a range of bird species (Newton 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the relationship between food availability and nestling condition or survival is not consistently positive, perhaps because factors like accessibility, prey profitability and nutrient composition are not always accounted for. Although some studies found improved nestling weight and survival when food availability around the nest was higher, for example for Yellowhammer Emberiza citrinella (Hart et al 2006), Linnet Carduelis cannabina (Bradbury et al 2003) and Corn Bunting Miliaria calandra (Brickle et al 2000;Boatman et al 2004), other studies could not detect such correlations for Chaffinch Fringilla coelebs (Bradbury et al 2003), Yellowhammer (Bradbury et al 2003) and Yellow Wagtail Motacilla flava (Gilroy et al 2009). For Skylarks, there are indications that nestling condition is significantly affected by the abundance of chick food within 100 m of the nest (Boatman et al 2004).…”
Section: Skylark Reproductionmentioning
confidence: 80%
“…A reduction in food availability during the breeding season can reduce the breeding success (e.g. Hart et al 2006). Secondly, especially in arable areas, farm specialisation may be a major cause of Barn Swallow population declines (Evans and Robinson 2004).…”
Section: Introductionmentioning
confidence: 99%